Implementing TQM - Sallis, Edward (Journal of Engineering Education Transformations, 2006)
Quality does not just happen. It must be planned for. Quality needs to be a major plank in all institution 's strategy, and needs to be approached systematically using a rigorous strategic planning process. Strategic planning is one of the major planks of TQM. Without clear long -term direction the institution cannot plan for quality improvement. The first of W Edward Deming's 14 points is "create constancy of purpose". This can only be achieved within the context of a corporate strategy. Underlying the strategy must be the concept of strengthening the customer focus. A strong strategic vision is one of the most important critical success factors for any institution. The strategic planning process in education can mirror that normally followed ill industry and commerce. The tools employed for establishing mission, goals and analyzing strengths, weaknesses, opportunities and threats translate well. The tools themselves are simple and easy to apply. Their power results from the focus they give to the corporate thinking process. They force a questioning of why the institution exists, for whom it exists, and whether it is pursuing the right goals.